USE OF INFORMATION TECHNOLOGIES - REQUIREMENTS FOR SCHOOL TRANSITION SPECIALIZED TRAINING - Grabchak Д.В.; Sharko В.Д. (Journal of Information Technologies in Education (ITE), 2011)
The article deals with the use of information - communication technologies in the work of teachers at the school for specialized education.